Bifurcation Analysis of a Reaction-Diffusion Mathematical Model of Mild Atherosclerosis - Mukherjee, Debasmita; Guin, Lakshmi Narayan; Chakravarty, Santabrata (Discontinuity, Nonlinearity, and Complexity, 2026)
A model addressing the phagocytosing process of macrophage ingesting oxidised LDL in atherosclerotic plaque formation is presented in this research manuscript. The biological phenomenon of plaque formation has been exposed here in terms of a reaction-diffusion model system in one spatial dimension (1D) by means of no-flux boundary conditions. The present article is mainly focused with the existence and stability of equilibrium solutions as obtained by the model parameters and interpretation of those results in terms of their potential bio-medical implications. Bifurcation analysis of the model system provides six relevant parameters of significance which are clinically sensible. A careful analysis of the model under submission provides an insight to the inflammatory route involved in the atherosclerotic plaque formation.